2003
DOI: 10.17221/5756-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Localization of immunoreactivities for neuropeptides and neurotransmitter-synthesizing enzymes in the pterygopalatine ganglion of the pig

Abstract: Study on the presence of the selected biologically active substances in nerve structures of the porcine pterygopalatine ganglion was performed with the use of immunofluorescence and RT-PCR. All neurons in the ganglion were ChAT-, VAChT-, NOS- and VIP- positive. However, some neurons displayed strong immunoreactivity, while in other neurons, immunoreactivity was moderate, or weak. Somatostatin (SOM) was present in approx. 11% of neurons. Tyrosine hydroxylase-positive (TH-positive) neurons were not detected, alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 24 publications
(21 reference statements)
2
25
2
Order By: Relevance
“…As a result, they are often used as models to study a variety of disease mechanisms and different pathophysiological conditions in humans, such as obesity and gastrointestinal dysfunctions (Spurlock and Gabler 2008;Pidsudko et al 2011;Zhang et al 2013). Substance P was reported to be localised in the porcine central nervous system (Barnes et al 1993;Holm et al 1993) and in the nerve fibres innervating many porcine organs (Schmidt et al 1991;Happola et al 1993;Czaja et al 2001;Lamb and Sparrow 2002;Podlasz et al 2003;Pidsudko et al 2008;Podlasz and Wasowicz 2008;Kaleczyc et al 2010). In the pig, substance P can stimulate both endocrine and exocrine pancreatic functions through NK-1 receptors (Schmidt et al 2000).…”
mentioning
confidence: 99%
“…As a result, they are often used as models to study a variety of disease mechanisms and different pathophysiological conditions in humans, such as obesity and gastrointestinal dysfunctions (Spurlock and Gabler 2008;Pidsudko et al 2011;Zhang et al 2013). Substance P was reported to be localised in the porcine central nervous system (Barnes et al 1993;Holm et al 1993) and in the nerve fibres innervating many porcine organs (Schmidt et al 1991;Happola et al 1993;Czaja et al 2001;Lamb and Sparrow 2002;Podlasz et al 2003;Pidsudko et al 2008;Podlasz and Wasowicz 2008;Kaleczyc et al 2010). In the pig, substance P can stimulate both endocrine and exocrine pancreatic functions through NK-1 receptors (Schmidt et al 2000).…”
mentioning
confidence: 99%
“…In the rat and human, VIP could even serve as a marker of PPG neurons because in those species 99% of PPG neurons express this neuropeptide [9]. In the porcine PPG all VIP-ergic PPG neurons are cholinergic in nature [11]. The co-localization of CART and VIP is additionally regularly found in the mammalian intrapancreatic neurons [25], enteric neurons from the stomach [26], small intestine [27] and large intestine [28].…”
Section: Discussionmentioning
confidence: 99%
“…So far, no studies describing the co-localization pattern of CART and galanin in mammalian PPG are available. It has been immunohistochemically demonstrated that in the porcine PPG galanin-containing neurons constitute up to 6% of all neuronal perykarya [11]. It has been postulated that galanin-containing PPG neurons are considered as a source of nerve supply to blood vessels (ciliary artery and choroidal blood vessels) of the cat's eye [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the available literature there are some papers dealing with cranial ganglia in the pig. Until now immunohistochemical characteristics of the cilary (Kaleczyc et al 2005), otic (Lakomy et al 2002) and pterygopalitine ganglion (Sienkiewicz et al 1995, Podlasz et al 2003 were described. The above mentioned ganglia belong to the parasympathetic division of the autonomic nerve system.…”
Section: Introductionmentioning
confidence: 99%